2018
DOI: 10.1186/s12955-018-1033-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the LITHUANIAN version of the 19-item audit of diabetes dependent quality of life (ADDQOL – LT) questionnaire in patients with diabetes

Abstract: BackgroundCurrently there is no diabetes-specific quality of life (QOL) instrument available in Lithuanian language. We aimed to develop a Lithuanian version of a widely-used individualised instrument - the Audit of Diabetes Dependent Quality of Life questionnaire (ADDQOL-19) and assess the validity and reliability in patients with type 1 and type 2 diabetes mellitus (DM).MethodsThis study was conducted at the Primary Care and Endocrinology Outpatient Clinics in Vilnius. The ADDQOL was translated from the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
3
4
1
1
Order By: Relevance
“…The average weighted impact was −3.38. This AWI score was generally lower compared to those in other settings [19,20,28,[31][32][33], and it also differed significantly from the AWI (−1.69, p < 0.001) obtained in the multinational study [18]. This concurred with findings of a study that showed that the QoL of the Palestinian population ranked considerably lower than populations of the 17 pooled WHO International Field Trial countries using the WHO QoL questionnaire [10].…”
Section: Discussionsupporting
confidence: 84%
“…The average weighted impact was −3.38. This AWI score was generally lower compared to those in other settings [19,20,28,[31][32][33], and it also differed significantly from the AWI (−1.69, p < 0.001) obtained in the multinational study [18]. This concurred with findings of a study that showed that the QoL of the Palestinian population ranked considerably lower than populations of the 17 pooled WHO International Field Trial countries using the WHO QoL questionnaire [10].…”
Section: Discussionsupporting
confidence: 84%
“…The next domain on which DM had a negative impact was "holidays". According to the literature, DM certainly has a negative effect on the quality of holidays ( [4], [6], [7], [10]), but not as much as participants in the present study reported. This could be explained by the fact that holidays are an essential part of life of Greeks.…”
Section: Discussioncontrasting
confidence: 63%
“…This could be explained by the fact that holidays are an essential part of life of Greeks. Additionally, previous studies report a correlation between aging and deterioration in general QoL, due to the occurrence of complications ( [7], [8], [10]). However, in our study no such correlation was found.…”
Section: Discussionmentioning
confidence: 90%
“…Diabetes-specific quality of life 3. Domains impacted by diabetes 1.1 item 2.1 item 3.18 items Not applicable Abbatecola et al [ 65 ] Bak et al [ 66 ] Fung et al [ 67 ] Jannoo et al [ 68 ] Kong et al [ 69 ] Magwood et al [ 70 ] Soon et al [ 71 ] Turk et al [ 72 ] Visockiene et al [ 73 ] Wee et al [ 74 ] Zhang et al [ 75 ] Audit of Diabetes Dependent Quality of Life (ADDQOL)- 19 English Diabetes patients Quality of life 1. General quality of life 2.Diabetes-specific quality of life 3.…”
Section: Resultsmentioning
confidence: 99%